2017
DOI: 10.1177/2325967116686784
|View full text |Cite
|
Sign up to set email alerts
|

Youth Football Injuries: A Prospective Cohort

Abstract: Background:There are approximately 2.8 million youth football players between the ages of 7 and 14 years in the United States. Rates of injury in this population are poorly described. Recent studies have reported injury rates between 2.3% and 30.4% per season and between 8.5 and 43 per 1000 exposures.Hypothesis:Youth flag football has a lower injury rate than youth tackle football. The concussion rates in flag football are lower than in tackle football.Study Design:Cohort study; Level of evidence, 3.Methods:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 23 publications
0
35
2
Order By: Relevance
“…We report a higher incidence of concussion in this youth football sample (5.1%); the reported rate in prior studies ranged from 0.9% 12,14 to 4.4%. 13 These differences seem to be explained by data collection methods.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…We report a higher incidence of concussion in this youth football sample (5.1%); the reported rate in prior studies ranged from 0.9% 12,14 to 4.4%. 13 These differences seem to be explained by data collection methods.…”
Section: Discussioncontrasting
confidence: 41%
“…Peterson et al relied on team managers to provide injury reports, resulting in a very low reported concussion incidence of 0.9% per season. 14 Dompier et al analyzed data from the Youth Football Surveillance System, which used athletic trainer report, and they described concussion rates for 5-to 14-year old youth of 3.1%-3.5% annually. 12 Kontos et al collected data on 8-to 12-yearold youth using research coordinators present at games and coach contact weekly, and reported concussion rates more similar to ours (4.4%).…”
Section: Discussionmentioning
confidence: 99%
“…59 Examples of substitution or elimination controls in professional football could include replacing tackle football with the less injurious flag football. 26,62…”
Section: Applying An Occupational Epidemiological Framework To the Nflmentioning
confidence: 99%
“…At site 2, we observed two definitive injuries (clavicle fracture and a lower limb injury) and two instances where a player struck their head (one H2G, one H2B) and appeared shaken but returned to play on the next set. The lack of H2H contacts and the relatively low-peak impact severities (ΔV R ) would suggest that non-tackle football incurs a lower risk of head injury compared with other contact sports, confirming prior epidemiological studies 3 6 8. However, future work should incorporate systematic medical reporting to identify the risk of head injury and the associated injurious head biomechanics.…”
Section: Discussionmentioning
confidence: 55%
“…Head and face injuries in adult non-tackle football have been reported to account for 12%–55% of injuries 2–6. Concussion rates range from 2% to 23% of all injuries,2 3 6–8 with an incidence rate of 1.78 concussions per 1000 athlete exposures (AE, defined as one athlete participating in one game) 3. Peterson et al 8 determined that youth flag football players experienced a concussion incidence of 1.33 per 1000 AEs, which was more than tackle football players in the same study, similar to rates reported for youth tackle players elsewhere9–12 and less than youth rugby athletes 13–17.…”
Section: Introductionmentioning
confidence: 99%